Politeness and forms of treatment in Portuguese as a Non-native Language: A case study in a bilingual society - Cação Lopes Antão, Marta Alexandra (2021)
This study examines how a group of students use Portuguese as a non-native language, in relation to the politeness strategies used in directive illocutionary acts, as well as the use of forms of treatment in Portuguese. Our intention was to verify if there was a dissociation between the grammatical and pragmatic competence of the learners. This is in the context of the non-universal nature of politeness, and how it changes across different cultures. The directive acts we analyze include orders, requests, offers, invitations and proposals. Of these, the last three were included in the category of hybrid acts, since they also have a commissive dimension. The study of the forms of treatment considers the constant restructuring of social practices, as well as the subtleties and specificities of certain words. In the sociolinguistic analysis of students’ work, we highlighted factors such as multilingualism, the proximity of Romance languages and age. Based on the results we obtained, we observed that students are concerned about adapting the forms both to the purpose of the discursive acts and to the characteristics of the interlocutors. However, we conclude that the pragmatic competence of learners should be enhanced, taking into account the specificities of the interactions.